Memahami Kritik al-Qur’an terhadap Agama Lain - Mun'im Sirry (Qur'an and Hadith Academic Society, 2014)
This article discusses some Qur’anic verses which criticizes other religions, especially Jews and Christianity. The thesis of this article is that these criticisms reflect a conflict in the early Islam, and the formation of Muslim communal identity. At the end of the article, the writer discusses the most heated debate whether Islam abrogates previous religions.